Peran Perempuan Single Parent Dalam Mengasuh Anak Di Kecamatan Maritengngae Kabupaten Sidrap (Suatu Kajian Antropologi Gender) - Paramitha, Dyan (Phinisi Integration Review, 2018)
The study aims at examining (1) the change of roles of single parent women, (2) time allocation of single parent women in public domain and domestic domain, and (3) the parenting applied by sinle parent women toward their children. The type of this study is descriptive qualitative. Data were collected by employing observation, documentation, and in-depth interview techniques by involving 7 infomants. In this study, the selection of informants used purposive sampling technique, and the data validation employed source triangulation. The result of the study reveal that (1) the changes in single parenrt women are as follows: they are more responsible on their children, they feel more discipline, and the change is not only in behaviour but also in mindset particularly in making decisions, (2) time allocations conducted by single parent women are as follows: they did the domestic first and public work afterwards: likewise, after they did the public work, they will return to their domestic work, and (3) in nurturing their children, the single parent women apply democratic parenting and insill cultural values of Buginese namely siri’ and maintaining five aspects, namely assitinajang (decency), sipakatau (mutual respect), getteng (firm and consistent), dan lempu (honest) in daily lives.